2017
DOI: 10.1136/gutjnl-2016-312432
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic biomarker signature to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis

Abstract: ObjectiveCurrent non-invasive diagnostic tests can distinguish between pancreatic cancer (pancreatic ductal adenocarcinoma (PDAC)) and chronic pancreatitis (CP) in only about two thirds of patients. We have searched for blood-derived metabolite biomarkers for this diagnostic purpose.DesignFor a case–control study in three tertiary referral centres, 914 subjects were prospectively recruited with PDAC (n=271), CP (n=282), liver cirrhosis (n=100) or healthy as well as non-pancreatic disease controls (n=261) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(224 citation statements)
references
References 53 publications
10
211
1
2
Order By: Relevance
“…It has been found to be 85% sensitive, 94.9% specific, and has a diagnostic accuracy of 90% to distinguish PDAC from CP. Its negative predictive value is 99.9%, and false negative rate is only 11% [63].…”
Section: Laboratory Investigationsmentioning
confidence: 92%
“…It has been found to be 85% sensitive, 94.9% specific, and has a diagnostic accuracy of 90% to distinguish PDAC from CP. Its negative predictive value is 99.9%, and false negative rate is only 11% [63].…”
Section: Laboratory Investigationsmentioning
confidence: 92%
“…Metabolic biomarkers were also used to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis . In a case‐control metabolomics study performed using both GC‐MS and LC‐MS, a biomarker signature comprised of nine metabolites and additionally carbohydrate antigen 19‐9 was identified to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis with a sensitivity of 89.9% and a specificity of 91.3%, respectively.…”
Section: Applications Of Metabolomics In Clinical Pharmacologymentioning
confidence: 99%
“…A recent study by Mayerle et al . used both untargeted and targeted MS‐based approaches including lipidomics and showed that PDAC patients could be distinguished from CP patients, as well as from healthy controls . Using a case–control design, 914 subjects with PDAC ( n = 271), CP ( n = 282), liver cirrhosis ( n = 100), and healthy and non‐pancreatic disease controls ( n = 261) were recruited in three consecutive studies.…”
Section: Blood‐based Biomarkersmentioning
confidence: 99%